ORIENTASI PEMILIH TERHADAP FIGUR POLITIK (Studi Pemilu di Jawa Tengah) - Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
Several studies have been done on the elections in Indonesia concluded that voters are increasingly rational, unaffected by dogma and ideology, but more rational and realistic. This study aims to analyze the change in orientation of the voters against political figures in Central Java. The approach used in this research study is descriptive analysis. There are as many as 400 respondents and key informants involved in the study. This study concludes that individual figures who have seen the effect on the integrity of the option rather than political parties. Although most people still voted for the party, in the 2014 legislative elections, the individual is more important figure than a political party.